Effect of continued antifibrotic therapy after forced vital capacity decline in patients with idiopathic pulmonary fibrosis; a real world multicenter cohort study. (January 2022) - Adams, Colin J.; Shapera, Shane; Ryerson, Christopher J.; Assayag, Deborah; Johannson, Kerri A.; Fell, Charlene D.; Morisset, Julie; Manganas, Hélène; Kolb, Martin; Hambly, Nathan; Cox, Gerard; Khalil, Nasreen; et al.
Abstract: Rationale: Longitudinal data on the impact of continued, switched or discontinued antifibrotic therapy in patients with idiopathic pulmonary fibrosis (IPF) who have disease progression is needed. Objective: We hypothesized that ongoing antifibrotic use (versus discontinuation) in the setting of forced vital capacity (FVC) decline would be associated with less future decline and lower likelihood of a composite outcome of FVC decline, lung transplant, or death. Methods: We performed a multicenter cohort study using data from the Canadian Registry for Pulmonary Fibrosis in patients with IPF with FVC decline ≥10% over 6 months on antifibrotic therapy. The association of continued, switched or discontinued therapy with (1) further change in FVC and (2) a composite of FVC decline ≥10%, transplant, or death, in the subsequent 6 months, was assessed using adjusted linear and logistic regression modelling, respectively. Generalized estimating equations accounted for repeated observations per patient. Results: 165 patients had a decline in FVC ≥10% over 6 months while receiving antifibrotic therapy. Compared to continued use, antifibrotic discontinuation after FVC decline was associated with greater additional FVC decline (−207 mL 95%CI -353 to −62, p = 0.005) and higher odds of FVC decline ≥10%, transplant, or death (odds ratio 12.2 95%CI 1.2 to 130.5, p = 0.04). There was no difference between continued versus switched antifibrotic therapy. Conclusions: Ongoing antifibrotic therapy in the setting of FVC decline is associated with less future FVC decline and lower odds of FVC decline ≥10%, transplant, or death in a real-world cohort of IPF. Highlights: Real world data on antifibrotic use in the setting of FVC decline is needed. Antifibrotic use after FVC decline is associated with less future FVC decline. Staying on antifibrotic decreases the odds of FVC decline, transplant, or death. A minority of patients stop antifibrotic therapy in the setting of FVC decline.